Religion and Ethnicity Among Irish Americans in Savannah, Georgia - Smith, William L. (Research in the social scientific study of religion, 2006)
This paper focuses on the interrelationships between religion and ethnicity among members of Irish organizations in Savannah, Georgia. The scholarly literature is mixed regarding the impact these concepts have on each other. The link between religion and ethnicity is variable depending on a variety of situational factors. Our research found that white Catholics in Savannah were often considered to be Irish, even if they were not Irish, and if they were Irish they were considered Catholic, even if they were not Catholic. While we found that the frequency of attendance of religious services and the importance of religion in forming/maintaining ethnic identity are significantly related to the strength of one’s ethnic identity, the importance of family and membership in ethnic organizations are even more strongly related to the strength of one’s ethnic identity.